Collaborative Strategic Reading (CSR): Its Impact on Students' Reading Comprehension - Tiana, Delis Meta; Lestari, Rina; Aprillia, Aprillia; Rahayu, Siti (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2025)
The study intends to examine the efficacy of Collaborative Strategic Reading (CSR) in improving students' reading comprehension. This study employed a quantitative research methodology, namely a quasi-experimental design. The study included of 27 students in the experimental class and 24 students in the control class of the English Literature department at a private college in Jakarta. The researchers utilized a multiple-choice reading assessment to gather data for this inquiry. The results suggest that the use of collaborative strategic reading processes has a substantial influence on students' capacity to understand textual content. At a significance level of <0.05 (0.000 <0.05), the null hypothesis (H0) is rejected, indicating a statistically significant disparity in reading comprehension between the experimental class and the control class. By enhancing the quality of learning and improving reading results, collaboration is a crucial component of the teaching and learning process for the reading class.